1998
DOI: 10.1002/chin.199813065
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electron Withdrawing Substituents on Equatorial and Apical Phosphines Have Opposite Effects on the Regioselectivity of Rhodium‐Catalyzed Hydroformylation.

Abstract: Electron Withdrawing Substituents on Equatorial and Apical Phosphines Have Opposite Effects on the Regioselectivity of Rhodium-Catalyzed Hydroformylation.-Chelating diphosphines designed to coordinate in diequatorial or in apical-equatorial positions are synthesized. From Ir-complexes as models for catalytic species it is shown that only diequatorial coordination is observed for (I) complexes and only apical-equatorial coordination for (III) complexes. For (II) complexes, a mixture of diequatorial and apical-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In homogeneous catalysis, the catalyst selectivity can be adjusted by some electron withdrawing aryl substituents, or functional groups such as carboxylic acid, ester or ketone groups). [21][22][23][24][25] For instance, Wakamatsu et al found that the shift of carbon double bond was strongly influenced by the functional groups in functionalized internal alkenes. [22] Casey et al investigated the different effects of aryl substituents linked at equatorial and apical diphosphines ligand on the selectivity of n-aldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In homogeneous catalysis, the catalyst selectivity can be adjusted by some electron withdrawing aryl substituents, or functional groups such as carboxylic acid, ester or ketone groups). [21][22][23][24][25] For instance, Wakamatsu et al found that the shift of carbon double bond was strongly influenced by the functional groups in functionalized internal alkenes. [22] Casey et al investigated the different effects of aryl substituents linked at equatorial and apical diphosphines ligand on the selectivity of n-aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Casey et al investigated the different effects of aryl substituents linked at equatorial and apical diphosphines ligand on the selectivity of n-aldehyde. [25] In heterogeneous catalyst, the surface properties of catalysts are also very important, such as the surface functional groups, heteroatom doping and hydrophobicity-hydrophilicity balance, which can affect the catalytic activity and product selectivity. [26,27] However, to our knowledge, the influence of the surface properties on the catalytic performance of heterogeneous hydroformylation is rarely reported.…”
Section: Introductionmentioning
confidence: 99%